In Search of Social Acceptance: Self-Reported Academic Behaviors and Social Desirability in the Business Area - Meurer, Alison Martins; Costa, Flaviano (Advances in Scientific and Applied Accounting, 2023)
Objective: The research aimed at analyzing the association between self-reported academic behaviors and the social desirability of postgraduate master’s and doctoral students in the business area. Academic behaviors are positive or negative attitudes performed by students, while social desirability represents those who seek to build a socially accepted image, but that does not match reality. Method: For data collection, an online survey was carried out with postgraduate master's and doctoral students linked to Brazilian courses in the business area, obtaining 1,816 valid participations that were analyzed using the Mann-Whitney test and Spearman Correlation. Results: The results found indicate that there is a positive association between academic citizenship behaviors and social desirability and a negative association between counterproductive academic behaviors and social desirability. Contributions: Stimulating a culture anchored in socially accepted norms of conduct can prove to be effective in directing student behavior, as fostering students' social desirability can encourage them to minimize counterproductive academic behavior and maximize academic citizen behavior. These behaviors are responsible for shaping the Higher Education environment, being able to influence the development of scientific research and the context in which future teachers are formed.